Causality between allergic diseases and kidney diseases: a two-sample Mendelian randomization study - Peng, Zhe; Dong, Xinyu; Long, Yingxin; Li, Zunjiang; Wang, Yueyao; Zhu, Wei; Ding, Banghan (Frontiers in Medicine, 2024)
Background: Evidence from observational studies and clinical trials suggests that the allergic diseases (ADs) are associated with kidney diseases (KDs). However, the causal association between them remains to be determined. We used bidirectional two-sample mendelian randomization (MR) analysis to evaluate the potential causality between them. Methods: MR was performed using publicly available genome-wide association study (GWAS) summary datasets. Inverse variance weighted (IVW), weighted median, MR-Egger regression, simple mode, and weighted mode methods are used to evaluate the causality between ADs and KDs. Sensitivity and heterogeneity analyses were used to ensure the stability of the results. Results: The MR results indicated that genetic susceptibility to ADs was associated with a higher risk of CKD [odds ratio(OR) = 1.124, 95% CI = 1.020 - 1.239, p = 0.019] and unspecified kidney failure (OR = 1.170, 95% CI = 1.004 - 1.363, p = 0.045) but not with kidney stone, ureter stone or bladder stone (OR = 1.001, 95% CI =1.000 - 1.002, p =0.216), other renal or kidney problem (OR = 1.000, 95% CI = 1.000 - 1.001, p = 0.339), urinary tract or kidney infection(OR = 1.000, 95% CI = 0.999 - 1.001, p = 0.604), kidney volume (OR = 0.996, 95% CI = 0.960 - 1.033, p = 0.812) and cyst of kidney(OR = 0.914, 95% CI = 0.756 - 1.105, p = 0.354). No causal evidence of KDs on ADs was found in present study. Conclusions: Results from MR analysis indicate a causal association between ADs and CKD and unspecified kidney failure. These findings partly suggest that early monitoring of CKD risk in patients with ADs is intentional.